DETERMINATION OF THE GAMES PLAYED BY PRE-SERVICE TEACHERS IN THEIR CHILDHOOD - Osman DALAMAN (International Journal of Eurasia Social Sciences, 2017)
The child learns behaviors, information and skills needed to live through games. Within games, children understand and internalize how human relations work, how communication occurs, how to gain access to information and roles such as man-woman, student-teacher etc. From the birth of a child, games allow the child to use many of his/her senses during the learning process and thus help the child to understand the world more quickly. Researchers have revealed that children who do not play or rarely play have brains 20 or 30 percent smaller than those of their game playing peers and toys stimulate 25% more brain synapses per neuron. Games contributing to physical, emotional and social development of children have also positive effects on children’s linguistic development and personality development. Moreover, games promote the effective functioning of children’s digestive systems, circulation systems and improve their hand-eye coordination and contribute to their small and large muscle development. Games and toys that are tools of games are an important part of a child’s life; they prepare children for the adult life by providing opportunities to develop their personalities and skills. The game has an indispensible role in a child’s life. Each child has a right to play. The child learns while playing; the place of games in a child’s life is indisputable. What inculcates the culture of game in a child is pre-school education and elementary school education. In the literature review conducted within the context of the current study, no such study has been encountered. As this is the first study on this topic in the literature, it is believed to make an important contribution to the relevant literature. The aim of this study is to determine the cultural games played with the child’s of the candidate teachers who studies in Science Teaching, Math Teaching, Pre-school Teaching and Social Science Teaching by candidate teachers who studying at Musical Education, Pre-school Education, Special Education, German Literature Teaching, Social Science Education and Computer Teaching. Descriptive Survey Model is used on this study. The enviroment of this study is composed by Necmettin Erbakan University and the sample of this study is composed by the candidate teachers who studies at Musical Education, Pre-school Education, Special Education, German Literature Teaching, Social Science Teaching and Computer Teaching in the spring term of 2015-2016. As the data collection tool, the Questionnaire to Determine the Games Played by the Pre-service Pre-school Teachers and Pre-service Classroom Teachers in their Childhood (OÖAÇOKO) developed by the researcher after seeking expert opinion was used. In the data collection process, a questionnaire was applied to determine the personal information of the prospective teachers and to not play a game consisting of questions about the cultural games they play in their childhood. The collected data were analyzed using SPSS 22 program and Microsoft Excell program.The obtained results will be tabulated and then interpreted.